Sodium selenite induces apoptosis via ROS‐mediated NF‐κB signaling and activation of the Bax–caspase‐9–caspase‐3 axis in 4T1 cells. Issue 3 (14th September 2018) - Zhang, Tao; Zhao, Gan; Zhu, Xinying; Jiang, Kangfeng; Wu, Haichong; Deng, Ganzhen; Qiu, Changwei
Abstract: Sodium selenite (SSE), a source of inorganic selenium, has been widely used as a clinical cancer treatment, but the precise molecular mechanisms of SSE remain to be elucidated. Our in vitro experiments have confirmed that SSE treatment causes a transient increase in intracellular reactive oxygen species (ROS) levels, resulting in the inhibition of nuclear transcription factor‐κB (NF‐κB) signaling and p65 and nuclear factor of kappa light polypeptide gene enhancer in B‐cells inhibitor, alpha phosphorylation levels in 4T1 cells. The inhibition of NF‐κB subsequently increased the expression of the apoptosis gene B‐cell lymphoma‐2‐associated X (Bax) and downregulated the transcription of antiapoptosis genes, such as B‐cell lymphoma‐2, cellular inhibitor of apoptosis 1, and X‐linked inhibitor of apoptosis. Additionally, the accumulation of ROS caused mitochondrial dysfunction, leading to the activation of caspase‐9 and ‐3, thereby resulting in apoptosis. However, modulation of the ROS level by the chemical inhibitor N‐acetyl‐cysteine reversed these events. Similarly, in vitro murine syngeneic breast tumor models showed that SSE inhibits tumor growth by promoting apoptosis. These results indicate that SSE induces apoptosis via ROS‐mediated inhibition of NF‐κB signaling and activation of the Bax–caspase‐9–caspase‐3 axis. Abstract : In this study, we found that sodium selenite (SSE) induces apoptosis via reactive oxygen species–mediated inhibition of nuclear transcription factor‐κB signaling and activation of the mitochondria‐related apoptosis pathway in vivo and in vitro. Exploration of the detailed molecular mechanisms underlying the efficacy of SSE in malignant cancer treatment is of great significance for translational medicine.